'Magnus's vision of a resurgent Scotland was elusive as a unicorn': Scottish Nationalism in Eric Linklater's Magnus Merriman. Issue 2 (November 2021) - Gilbert, Adam
Abstract : Eric Linklater's 1934 novel Magnus Merriman is recognised as a comic triumph for its satirical treatment of the Scottish Renaissance and the associated contemporary Scottish nationalist movement. This article argues that Magnus Merriman has deceptive depth because Linklater offers frequently profound insights into a compelling point in Scottish cultural and political history. The misadventures of the eponymous Magnus have strong parallels with Linklater's own belated entry into the Scottish Literary Renaissance and his disastrous attempt at standing for parliament as a Scottish nationalist candidate. The novel showcases Linklater's idiosyncratic political doctrine of 'small nationalism', and his unflattering portrayal of the National Party of Scotland is coloured by his disillusionment with it. The doomed poem written by Magnus, ' The Returning Sun', symbolises the Scottish Renaissance, reflecting its shortcomings and the difficulty of forming a unified Scottish cultural identity. The character of Magnus himself embodies the lack of a single, coherent Scottish identity as a Scottish Renaissance anti-hero. Magnus's political and literary disappointments mean Linklater gives a pessimistic assessment of the relative failure of the Scottish Renaissance and the nationalist movement of the period. Linklater's irreverent examination of Scottish nationalism retains contemporary relevance. Magnus Merriman is more than just a hilarious comedy and represents a significant contribution to Scottish literature.